Respuesta :

gmany

Answer:

[tex]\large\boxed{\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}=\dfrac{x^6}{2y^4}}[/tex]

Step-by-step explanation:

[tex]\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}\qquad\text{use}\ (ab)^n\ \text{and}\ (a^n)^m=a^{nm}\\\\=\dfrac{2^3(x^3)^3y^3}{4^2x^2(y^2)^2xy^3}\qquad\text{cancel}\ y^3\\\\=\dfrac{8x^{(3)(3)}y^3\!\!\!\!\!\diagup}{16x^2y^{(2)(2)}xy^3\!\!\!\!\!\diagup}\\\\=\dfrac{8\!\!\!\!\diagup^1x^9}{16\!\!\!\!\!\diagup_2x^2y^4x}\qquad\text{use}\ a^na^m=a^{n+m}\\\\=\dfrac{x^9}{2x^{2+1}y^4}\\\\=\dfrac{x^9}{2x^3y^4}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\=\dfrac{x^{9-3}}{2y^4}\\\\=\dfrac{x^6}{2y^4}[/tex]